The Spiritual in Art : Abstract Painting 1890-1985. - Tuchman, M. (New York : Abbeville Press, 1986)
Antrim, Craig ; Arp, Hans (Jean) ; Balla, Giacomo ; Beuys, Joseph ; Bianchi, Domenico ; Bisttram, Emil ; Ceccobelli, Bruno ; Charchoune, Serge ; Cramer, Konrad ; Crotti, Jean ; Delaunay, Robert ; Delville, Jean ; Denis, Maurice ; van Doesburg, Theo ; Dove, Arthur ; Duchamp, Marcel ; Duchamp, Suzanne ; Ender, Boris ; Federle, Helmut ; Filiger, Charles ; Fontana, Lucio ; Gauguin, Paul ; Giacometti, Augusto ; Gosewitz, Ludwig ; Gottlieb, Adolph ; Graves, Morris ; Harris, Lawren ; Hartley, Marsden ; Hedrick, Wally ; van Heemskerck, Jacoba ; Hodler, Ferdinand ; Hugo, Victor ; Irwin, Robert ; Itten, Johannes ; Jensen, Alfred ; Jensen, Bill ; Jess ; Johns, Jasper ; Jonson, Raymond ; Kandinsky, Wassily ; Kelly, Ellsworth ; Khnopff, Fernand ; Klee, Paul ; Klein, Yves ; Klint, Hilma af ; Kliun, Ivan ; Kudriashev, Ivan ; Kupka, Frantisek ; Malevich, Kasimir ; Marc, Franz ; Marden, Brice ; Matiushin, Mikhail ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; McLaughlin, John ; Merz, Mario ; Mondriaan, Piet ; Morgner, Wilhelm ; Muche, Georg ; Mullican, Lee ; Mullican, Matt ; Munch, Edvard ; Nauman, Bruce ; Newman, Barnett ; O'Keeffe, Georgia ; Onslow-Ford, Gordon ; Orr, Eric ; Paalen, Wolfgang ; Pelton, Agnes ; Picabia, Francis ; Pinkham Ryder, Albert ; Plasschaert, Albert A. ; Polke, Sigmar ; Pollock, Jackson ; Pousette-Dart, Richard ; Rainer, Arnulf ; Ranson, Paul ; Redon, Odilon ; Reinhardt, Ad ; Rockburne, Dorothea ; Rothko, Mark ; Schwitters, Kurt ; Sérusier, Paul ; Severini, Gino ; Smith, Tony ; Tack, Augustus Vincent ; Taeuber-Arp, Sophie ; Thorn-Prikker, Johan ; Tobey, Mark ; Toorop, Jan ; Vantongerloo, Georges ; de Winter, Janus ; Wudl, Tom ; Zammitt, Norman
The Spiritual in Art : Abstract Painting 1890-1985, Los Angeles County Museum of Art, Los Angeles, 23 November 1986 - 8 March 1987 ; Museum of Contemporary Art, Chicago, 17 April - 19 July 1987 ; Haags Gemeentemuseum, Den Haag, 1 September - 22 November 1987
boek